Design and development of robotic invigilator - Tint, Hlyan Yu. (2012)
Nowadays, school exams and various professional tests have become an important platform to test candidates’ academic ability or professional skill. However, these exams or tests, especially when a large number of people are involved, are usually associated with high manpower costs. These manpower costs arise from the large number of human invigilators deployed in the exam setting.